Epidural versus Patient-Controlled Analgesia after Pediatric Thoracotomy for Malignancy: A Preliminary Review - Gonzalez, Katherine W.; Dalton, Brian G.; Millspaugh, Daniel L.; Thomas, Priscilla G.; St Peter, Shawn David (European Journal of Pediatric Surgery, 2016)
Introduction The use of thoracic epidural is standard in adult thoracotomy patients facilitating earlier mobilization, deep breathing, and minimizing narcotic effects. However, a recent randomized trial in pediatric patients who undergo repair of pectus excavatum suggests patient-controlled analgesia (PCA) produces a less costly, minimally invasive postoperative course compared with epidural. Given that thoracotomy is typically less painful than pectus bar placement, we compared the outcomes of epidural to PCA for pain management after pediatric thoracotomy.Methods A retrospective review of 17 oncologic thoracotomies was performed at a children's hospital from 2004 to 2013. Data points included operative details, epidural or PCA use, urinary catheterization, days to regular diet, days to oral pain regimen, postoperative pain scores, length of stay, and anesthesia charges. Patients were excluded if they did not have epidural or PCA following thoracotomy.Results Six thoracotomies were managed with an epidural and 11 with a PCA. Three epidural patients were opiate naïve compared with two with a PCA. The most common indication for thoracotomy was metastatic osteosarcoma (n = 13). When comparing epidural to PCA, there was no significant difference in days to removal of Foley catheter, regular diet, oral pain control, length of stay, or total operating room time. Postoperative pain scores were also comparable. The mean anesthesia charges were significantly higher in patients with an epidural than with a PCA.Conclusion Epidural catheter and PCA provided comparable pain relief and objective recovery course in children who underwent thoracotomy for oncologic disease; however, epidural catheter placement was associated with increased anesthesia charges, suggesting that PCA is a noninvasive, cost-effective alternative.
Keywords: pediatric; thoracotomy; epidural; patient-controlled analgesia